Tantra, Ritual Performance, and Politics in Nepal and Kerala : Embodying the Goddess-clan - Martin, Matthew (Religious Studies, Theology and Philosophy E-Books Online, Collection 2020, ISBN: 9789004419094., 2021)
In previous studies of South Asian Tantric ritual, scholars tend to focus on one region or context. For the first time, Tantra, Ritual Performance and Politics in Nepal and Kerala: Embodying the Goddess-clan offers a comparative approach to Tantric mediumship as observed in two locales: Navadurgā rituals in Bhaktapur, Nepal, and Teyyāṭṭam in North Kerala. In this book, Matthew Martin advances a new theory of ritual, which spotlights the way dancer-mediums embody medieval goddess-clans and ancestor deities, through offerings of food and sacrifice, that synchronize their denizens with the land in spiralling web-like ritual networks. Uniquely interdisciplinary in style, this study synthesizes cultural history, ethnography, and theory to explore the continuities - historical, societal, and political - that characterize these ritual traditions across the subcontinent.